Incidence and Clinical Outcomes of Premature Infants: 1‐Year Retrospective Study at the NICU of Gadarif Teaching Hospital - Mohammed Ahmed Abdellah Ahmed; Elshazaly Saeed; Elnazeir Mohamed Ibrahim Mohamedzain; Mohamed Salah Abdulrazeg Abdulrahman; Suleman Sofian Suliman; Ahmed Mohammed Ahmed Abdellah; A. L. Sir Ahmed Addalla Ahmed; Sohaib Mohammed Mokhtar Ahmed (Health Science Reports, 2026)
ABSTRACT Background Prematurity remains a leading cause of neonatal morbidity and mortality worldwide, with the highest burden in low‐resource settings such as sub‐Saharan Africa. Reliable local data are limited in Sudan, particularly in Eastern states. This study aimed to determine the incidence, maternal risk factors, neonatal characteristics, and outcomes of premature infants admitted to the NICU at Gadarif Teaching Hospital. Methods A retrospective observational study was conducted from July 2024 to July 2025. Medical records of all neonates admitted to the NICU were reviewed. Preterm birth was defined as delivery before 37 completed weeks of gestation. Maternal, perinatal, and neonatal variables were extracted. Logistic regression models were used to identify predictors of preterm birth and mortality. Results Of 604 neonates, 198 (32.8%) were preterm. Mothers of preterm infants were younger (24.3 ± 6.5 vs. 26.4 ± 6.6 years, p = 0.002). Elective cesarean delivery and lower parity were associated with prematurity. Pre‐eclampsia was significantly more common among preterm births (4.0% vs. 1.5%, p = 0.049). Preterm neonates had markedly lower mean birth weight (1.7 ± 2.4 kg vs. 3.0 ± 1.6 kg, p < 0.001) and higher rates of sepsis (71.7%), respiratory distress (62.6%), and jaundice (24.7%). Mortality was significantly higher among preterm infants compared to term (29.4% vs. 7.8%, p < 0.001). In multivariable analysis, younger maternal age increased risk of prematurity, while higher gestational age (aOR 0.58, p = 0.002) and antenatal care attendance (aOR 0.26, p = 0.032) reduced mortality. Conclusion Prematurity constituted nearly one‐third of NICU admissions in this cohort and was associated with high mortality. Strengthening antenatal care, delaying early pregnancies, and improving NICU capacity may reduce the burden of preterm related deaths in this setting, although further studies are needed.